Intellectual capital and profitability: a firm value approach in the European companies - Martins, M. M. (2016)
Intangibles are, at a knowledge-based economy, the most important resources, driving companies towards systematic and sometimes unexpected returns. This paper follows a positivist approach and aims to investigate the association between the degree of intangibility, value of firms and their profitability. Based on the 500 largest European companies, rated by Financial Times, the most relevant insights emerge from the association between firms’ knowledge intensity level and its degree of profitability. These insights consolidate the evidences that immaterial resources act as drivers of future benefits and are embodied on firms’ profitability ratios.